Why do low- and high-skill workers migrate?: flow evidence from France - Dominique M. Gross; Nicolas Schmitt (Center for Economic Studies and ifo Institute (CESifo), 2006)
With a focus on the role of cultural clustering and income distribution, this paper investigates whether standard determinants influence international migration of workers to France with the same intensity across different skill levels and with or without free mobility. We find that low-skill migrants respond to most push and pull migration factors. High-skill migrants however respond only to financial incentives and cultural clustering does not matter. Migration policy is effective at controlling flows of low-skill migrants but free mobility has no impact on high-skill flows. Hence, France must rely on growing earnings and skillpremium to attract high-skill workers from high income countries.
Keywords: F22; J24; O24; 330